Angas-Sura Etymologies VII - Takács, Gábor (Lingua Posnaniensis, 2020)
The paper as part of a long-running series is devoted to the etymological analysis of a new segment (namely that with initial dental *d-) of the Angas-Sura root stock, a small group of modern languages remotely and ultimately akin to pharaonic Egyptian and the well-known Semitic languages or Twareg in the Sahara etc. Doing so, I wish to continue the noble tradition initiated by J.H. Greenberg (1958), the founding father of modern Afro-Asiatic comparative linguistics (along with I.M. Diakonoff), who was the first scholar ever to have established by Neo-Grammarian the methods regular consonantal correspondences between Angas-Sura and ancient Egyptian in his pioneering (painfully isolated) paper on the ancient trichtomomy of the word-initial labials in both branches. Nowadays our chances in following this path are substantially more favourable being equipped with our gigantic comparative root catalogue system of the Egyptian etymologies ever published (ongoing since 1994) and of the Afro-Asiatic parental lexical stock (ongoing since 1999).